SINTESIS SILIKA MESOPORI TERSULFONASI DARI ABU DAUN BAMBU PETUNG (Dendrocalamus asper) - Precelia, Sari Clara; Subagyono, RR Dirgarini Julia Nurlianti; Saleh, Chairul (Jurusan Kimia FMIPA UNMUL, 2018)
Research on the synthesis of sulfonated mesoporous Silica from bamboo leaves ash (Dendrocalamus asper) as Heterogeneous Acid Catalyst has been conducted. Bamboo Leaf Ashfish serves as a source of silica for the manufacture of Mesoporous Silica. The research phase consisted of synthesis of MSU-H with surfactant template method, mesoporous silica modification with 3-mercaptopropyl-trimethoxysilane (MPTMS) using post grafting method. The mesoporous silica has a pore volume of 1.03 cm3/g, a surface area of 150 m2/g and a pore diameter of 27.5 nm. The FT-IR spectrum of mesoporous silica before sulfonation shows the presence of Si-O-Si, and Si-OH functional groups while that of Mesoporous silica after sulfonation shows the presence of Si-O-Si, Si-O, Si-OH and –SO3H functional groups.